Corrosion behaviour of crystalline and amorphous forms of the glass forming alloy Fe43Cr16Mo16C15B10 - Bakare, M.S.; Voisey, K.T.; Chokethawai, K.; McCartney, D.G. (Elsevier, 2012)
The corrosion behaviour of both crystalline and largely amorphous forms of the Fe-based glass forming alloy, Fe43Cr16Mo16C15B10 alloy was investigated. Two different methods were used to induce transformation to the amorphous form of the alloy: laser melting and HVOF spraying. Both methods produced largely amorphous material, however the high brittleness of the alloy makes it susceptible to cracking during laser treatment, hence this technique is not suitable for largescale application. Potentiodynamic scanning showed that in 0.5M H2SO4 and 3.5% NaCl electrolytes both amorphous forms of the alloy had better corrosion resistance (lower current densities for -200 to +1000mV SCE) compared to the crystalline material. The laser treated material and HVOF coating performed similarly in 3.5% NaCl. In 0.5M H2SO4 the HVOF coating had a lower current density than the laser melted material for almost all of the potential range -300 to +1000mV SCE. The improved corrosion behaviour of the largely amorphous material is attributed to its homogeneity, and particularly to the elimination of the Mo-rich phase that underwent preferential corrosion in the crystalline form of the material.